Bacteriological analysis of potable water in areas with reported cholera outbreaks in Ogun, Oyo and Lagos States, Nigeria - Deji-Agboola MA; Museliu O; Olajubu FA; Osinuoebi OA; Idowu AO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2017)
Background: Cholera outbreaks, reported yearly in Nigeria, are a public health concern and transmission is attributed to drinking of contaminated water and poor sanitation. Objective: To conduct a bacteriological analysis of potable water in areas with reported cholera outbreaks in Ogun, Lagos and Oyo States. Methods: Water samples collected from the study areas were examined physically, cultured in MacConkey broth and Alkaline peptone water to determine the most probable number (MPN) of Coliforms and isolate Vibro species respectively. Bacteria were cultured from the broths and were identified using standard methods. Results: All the other water samples examined were colourless, odourless, tasteless and lack particles except the well water which had yellowish brown colouration (4; 8%) and contained visible particles (5; 30%). The presumptive total coliform count ranged between < 3 and 1,100 MPN /100ml. Enterobacter gergoviae (34; 47.2%), Escherichia coli (16; 22.2%), Klebsiella pneumonia (7; 9.7%), Sarratia liquefaciens (6; 8.3%), Vibrio parahaemolyticus (5; 6.9%), Citrobacter diversus (2; 2.8), Klebsiella oxytoca (1; 1.4%) and Enterobacter aerogenes (1; 1.4%) were isolated from 33.5% of the water samples. The level of contamination of water sources within the different study areas was significant (p<0.001). Vibrio cholerae was not isolated, but Vibrio parahaemolyticus was isolated from 5 (10%) of the well water samples. Thermo-tolerant Coliforms were also identified from some samples. Conclusion: The well water samples were grossly contaminated with coliform bacteria and Vibrio parahaemolyticus and should be treated before drinking.